Volatility, Money Market Rates, and the Transmission of Monetary Policy - Seth B. Carpenter; Selva Demiralp (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
We explore the effect of volatility in the federal funds market on the expectations hypothesis in money markets. We find that lower volatility in the bank funding markets market, all else equal, leads to a lower term premium and thus longer-term rates for a given setting of the overnight rate. The results appear to hold for the US as well as the Euro Area and the UK. The results have implications for the design of operational frameworks for the implementation of monetary policy and for the interpretation of the changes in the Libor-OIS spread during the financial crisis.
Keywords: E43; E52; E58; 330; Monetary transmission mechanism; expectations hypothesis; term premium; Geldpolitik; Geldpolitische Transmission; Geldmarkt; Volatilität; USA; Großbritannien; EU-Staaten